A current view of Canadian cardiorespiratory fitness - Bailey, D. A. (1974)
A standard Åstrand bicycle ergometer test was used to predict the maximum oxygen intake of 672 female and 558 male volunteers ranging in age from 15 to 69 years. In terms of this index of cardiorespiratory performance Canadians were unfit relative to Swedish norms. Also, some 47% of women and 40% of men achieved only low or fair fitness categories when evaluated relative to American Heart Association recommendations. These results are poorer than those reported for Torontonians in 1966. Men perceive their cardiorespiratory fitness accurately but women do not. In both sexes adequate recreational activity apparently leads to maintenance of cardiorespiratory fitness.